3D-CUBE readiness model for industry 4.0: technological, organizational, and process maturity enablers. Issue 1 (31st December 2022) - Felippes, Bruna; da Silva, Isaac; Barbalho, Sanderson; Adam, Tobias; Heine, Ina; Schmitt, Robert
ABSTRACT: This paper proposes a new Readiness Model, 3D-CUBE, to assess the current state of manufacturing companies in the digital transformation context. Using a systematic literature review with 8-Steps-Search-Flow and a hypothetical-deductive framework (considering maturity as an 'input' enabler and not as an 'output'), the best information of 63 existing models was selected from 486 studies found in 10 databases. The 3D-CUBE was elaborated, with 3 dimensions (X = Organizational, Y = Technological, and Z = Process Maturity), 6 sub-dimensions, and 21 elements, including a scale 0-5 to assess the company readiness level. For the company's Data Collection, a 3D-CUBE Questionnaire was developed, which provides a radar graph and calculates the company's score with a readiness vector R=(X, Y, Z). Based on the existing model's shortcoming, 3D-CUBE is a new contribution to this research stream, to help companies in getting ready for Industry 4.0. .